244 A Systematic Review of Modeling in Peyronie's Disease. (1st May 2022) - Krishnappa, P; Manfredi, C; Arcaniolo, D; Sinha, M; Moncada, I
ABSTRACT: Introduction: Penile modeling to correct the penile curvature in Peyronie's disease (PD) may be achieved manually (intra-operatively or post-injection) or by using assisted devices (penile traction, vacuum device or penile prosthesis). To the best of our knowledge this is the first systematic review of the literature comprehensively evaluating penile modeling procedures. Objective: To evaluate the efficacy, safety and satisfaction associated with penile modeling in patients with PD. Methods: A PROSPERO registered (CRD42021241729) systematic search in MEDLINE and Cochrane Library was done in accordance with PRISMA. PICO: Studies were deemed eligible if they assessed patients with PD (P) undergoing modeling procedures (I) with or without comparative group(C) evaluating the efficacy, safety or patient satisfaction (O). Results: A total of 23 studies, involving 1, 238 patients were included in the systematic review. The majority (n=13) studied penile traction therapy and the least being manual modeling at home and manual modeling after collagenase injection (1 each). The studies were of low and intermediate quality (mean Newcastle-Ottawa Scale score of 5.7 and mean Jadad score of 3.3) with a mean level of evidence of 3.4. The mean penile curvature at baseline was between 31 and 80.8 degrees. Nine (39.1%) studies found a significant improvement (p<0.05) of penile curvature after penile modeling, ranging between 11.7 and 37.2 degrees. A increase in mean stretched penile length was reported in 7 (30.4%) articles, varying between 0.4 and 1.8 cm. Serious complications such as penile prosthesis malfunctions (3.3%-11.1%) and urethral injuries (2.9%) were only reported for intra-operative manual modeling. Conclusion: Although individual studies have noted improvement in penile curvature and stretched penile length, specific recommendations regarding penile modeling in PD cannot be provided due to the inability to perform a pooled analysis of the included studies with significant heterogeneity and the absence of standardized methods to report complications and patient satisfaction. Further RCTs with adequate sample size, validated assessment tools and longer follow-up are needed. Disclosure: Work supported by industry: no. A consultant, employee (part time or full time) or shareholder is among the authors (Boston Scientific).